Structuring a Modern Web Service for Users and Search Engines - Ruohola, Eero (My University, 2021)
This thesis aims to study how search engines should be taken into account when developing an early stage web service. The thesis introduces practical methods for improving the presentation of a web service’s pages in search engine results and a general overview of the working principles of search engines is provided. The thesis also goes over the history of web search engines in general before covering the history of Google in a bit more detailed manner. The practical aspect of this thesis is conducted as a case study, where search engine legibility related improvements are made to the Skole application. Skole is a very early stage web service, were higher educations students can share knowledge and discuss their studies. The case study aims to get information about how and what kind of improvements can be made, and how they make a difference in practice. The case study also seeks to find out how important it is to follow the guidelines of search engine providers, when doing development for this kind of very early stage web service. The results of the case study will mainly be measured by documenting how the application’s pages show up in Google before and after changes have been made. Some aggregated data from analytics providers is also used to see how the made improvements have affected the usage of the application.
Keywords: Search Engines, Web Services, SEO, Google Search, PageRank, User Experience